Development of the engineering procedure for the thermotechnical calculation of a building envelope with air chambers and a heatreflecting coating - Suleimenov, Ulanbator; Kostikov, Andrii; Ristavletov, Raimberdy; Kambarov, Medetbek; Kudabayev, Ruslan; Vorontsova, Anna (Eastern-European Journal of Enterprise Technologies, 2020)
The study has addressed the development of the engineering procedure for the thermotechnical calculation of a building envelope with thermal insulation in which air chambers with a heat-reflecting coating are formed. The engineering procedure implied determining the average RSI-value of the building envelope based on the calculation of a temperature field in it. To find the temperature field, a one-dimensional heat conduction problem in a multilayer building envelope was considered. The thermotechnical heterogeneities caused by the presence of alternating air chambers and dividers of insulation material were taken into account in the mathematical model using the effective thermal conductivity of a corresponding layer. This coefficient takes into consideration the convective and radiant components of heat transfer through air chambers. An expression was obtained for determining its value depending on the temperature at the junction of corresponding layers with adjacent building envelope layers. The iterative procedure was proposed that makes it possible to use this expression for determining the temperature fields in the building envelope under consideration. The geometric and thermophysical characteristics of building envelope elements, as well as the values of indoor and outdoor temperature and heat transfer coefficients of the corresponding surfaces, were used as initial data. The engineering procedure was verified by comparison with the results of three-dimensional CFD simulation, which takes into detailed account the free-convective motion in air chambers and the radiation heat exchange between thermally inhomogeneous walls of the air chamber. It was shown that the use of a one-dimensional mathematical model instead of a detailed three-dimensional one leads to errors not exceeding 2.5 %. As a result of our comparative analysis, the effectiveness of the proposed thermal insulation material having air chambers with a heat-reflecting coating was shown in comparison with the conventional approaches to building envelope thermal insulation. Calculations were performed for the case of the coldest five-day period in the climatic zone of Shymkent (Republic of Kazakhstan)